2018
DOI: 10.1021/acs.jpcc.7b11054
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Understanding of Catalyst Activation: Carboxylic Acid Solutions, but Not the Acid Itself, Increase the Reactivity of Anatase (001) Faceted Nanocatalysts

Abstract: Our ability to predict nanocatalyst reactivity has been hindered by our lack of atomic-scale understanding of nanocatalyst surface structure. Do nanocatalyst surfaces adopt a bulk-terminated structure or do they reconstruct to minimize their free energy, thereby lowering their reactivity as often observed in vacuum? Similarly, do nanocatalysts processed at high temperatures maintain their low reactivity, reconstructed surfaces when used at low temperatures? Using a new technique for the preparation of anatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…III D, Table II). However, the adsorption structure at half coverage agrees well with the experimental and theoretical results from DeBenedetti et al 33…”
Section: A Hydrohalic and Carboxylic Acid Adsorptionsupporting
confidence: 88%
See 2 more Smart Citations
“…III D, Table II). However, the adsorption structure at half coverage agrees well with the experimental and theoretical results from DeBenedetti et al 33…”
Section: A Hydrohalic and Carboxylic Acid Adsorptionsupporting
confidence: 88%
“…The difference of the findings may be due to the different functionals and computational settings used. On the other hand, in accordance with the results presented here, a combined experimental and theoretical study found that the reconstruction is not the thermodynamic ground state in benzoic acid and HF aqueous solutions and only formed at temperatures above 550 ○ C. 33 Furthermore, the aforementioned substitution of surface hydroxyl groups by halide ions also releases the tensile stress on the unreconstructed (001) surface. Since this eliminates the driving force for the reconstruction, the substitution process will also lift the reconstruction.…”
Section: Lifting Of the (001) 1 × 4 Reconstructionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, due to higher surface energy of (001) facet, it undergoes 1×4 reconstruction at ultrahigh vacuum and higher temperature [39][40][41][42][43] . The reactivities of the reconstructed (001)-(1×4) surface needs to be understood further for its practical implications [44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…The surface structure of metal oxides dictates their surface properties through the coordination, arrangement, and electronic structure of the topmost atoms [13][14][15][16][17][18][19][20]. Hence, it is important to map out the parameter space of the equilibrium surface phases of these materials, including their evolution with µ O .…”
mentioning
confidence: 99%